2021
DOI: 10.2480/agrmet.d-20-00013
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon flux research in the Asian region: Review and future perspectives

Abstract: Soil respiration R s is the largest flux of carbon dioxide CO 2 next to photosynthesis in terrestrial ecosystems. With the absorption of atmospheric methane CH 4 , upland soils become a large CO 2 source and CH 4 sink. These soil carbon C fluxes are key factors in the mitigation and adaption of future climate change. The Asian region spans an extensive area from the northern boreal to tropical regions in Southeast Asia. As this region is characterised by highly diverse ecosystems, it is expected to experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 364 publications
(290 reference statements)
0
1
0
Order By: Relevance
“…Thus, PAR was considered to be the primary driver for NEE during the growing season at the diurnal time scale. Previous studies have also demonstrated that carbon absorption is largely affected by PAR (Yang et al, 2011;Jia et al, 2014), whereas carbon release is mainly controlled by temperature (Sha et al, 2021).…”
Section: Discussion Diurnal Variation In Net Ecosystem Co 2 Exchangementioning
confidence: 98%
“…Thus, PAR was considered to be the primary driver for NEE during the growing season at the diurnal time scale. Previous studies have also demonstrated that carbon absorption is largely affected by PAR (Yang et al, 2011;Jia et al, 2014), whereas carbon release is mainly controlled by temperature (Sha et al, 2021).…”
Section: Discussion Diurnal Variation In Net Ecosystem Co 2 Exchangementioning
confidence: 98%
“…The ratio of R h to R s varied from 10 to 90% in terrestrial ecosystems, depending on vegetation types and seasonal variations [12]. On average, R a contributed 45.8% in forest ecosystems and 60.4% in non-forest ecosystems to R s [13]. Based on soil FCO 2 data from 54 forest sites, we summarized that R a and R h were approximately evenly partitioned, ranging between 50 and 60% [4].…”
Section: Introductionmentioning
confidence: 90%